Functional characterization of C-TERMINALLY ENCODED PEPTIDE (CEP) family in Brassica rapa L - Ziwen Qiu; Keqing Zhuang; Yiting Liu; Xiaomin Ge; Chen Chen; Songping Hu; Huibin Han (Plant Signaling & Behavior, 2022)
The small regulatory C-TERMINALLY ENCODED PEPTIDE (CEP) peptide family plays crucial roles in plant growth and stress response. However, little is known about this peptide family in Brassica species. Here, we performed a systematic analysis to identify the putative Brassica rapa L. CEP (BrCEP) gene family. In total, 27 BrCEP genes were identified and they were classified into four subgroups based on the CEP motifs similarity. BrCEP genes displayed distinct expression patterns in response to both developmental and several environmental signals, suggesting their broad roles during Brassica rapa development. Furthuremore, the synthetic BrCEP3 peptide accelerated Brassica rapa primary root growth in a hydrogen peroxide (H2O2) and Ca2+ dependent manner. In summary, our work will provide fundamental insights into the physiological function of CEP peptides during Brassica rapa development.